Radius of Strong Starlikeness for Some Classes of Analytic Functions - Keerthi, B Srutha; Gangadharan, A; Chinthamani, S (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
Let Ï†(z) be an analytic function with positive real part on âˆ† = z; |z| < 1 with Ï†(0) = 1, Ï† 0 (0) > 0 which maps the unit disk âˆ† onto a region starlike with respect to 1 and symmetric with respect to theÂ real axis. The radii of strong starlikeness of certain classes of analyticÂ functions are computed.